Proceedings of the 3rd Global Conference on Business, Management, and Entrepreneurship (GCBME 2018) 2020
DOI: 10.2991/aebmr.k.200131.048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Characteristics to Employee’s Performance: A Case Study on Employees at Interior Industry

Abstract: Every organization is trying to achieve their goals. Factors to improve the development and progress of the company cannot be separated from the role of human resources that move the organization within the company. Employee performance is still an important problem in manufacturing companies, especially in CV. Saputra Jaya in Cimahi. One of the company's efforts to improve employee performance is by improving the understanding of the characteristics of an employee's job. The present study uses descriptive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Along with the other aspects of work characteristics, task identity has been shown to improve productivity and overall employee performance (Humphrey et al, 2007). Senen et al (2018) in their study found that job factors had a favourable impact on employee performance. And a scientific investigation by Nidaul Izzah et al ( 2019) demonstrates there's a favourable relationship between work characteristics and employee performance.…”
Section: Work Characteristics and Employee Performancementioning
confidence: 97%
See 2 more Smart Citations
“…Along with the other aspects of work characteristics, task identity has been shown to improve productivity and overall employee performance (Humphrey et al, 2007). Senen et al (2018) in their study found that job factors had a favourable impact on employee performance. And a scientific investigation by Nidaul Izzah et al ( 2019) demonstrates there's a favourable relationship between work characteristics and employee performance.…”
Section: Work Characteristics and Employee Performancementioning
confidence: 97%
“…A recent study by Pusparini (2023) discovered that work characteristics improve employee performance. Employee performance is affected by job characteristics; if job characteristics are well understood, employee performance improves (Senen et al, 2018). Task significance, a work attribute, influences individual performance at work (Lopez-Cabarcos et al, 2022).…”
Section: Work Characteristics and Employee Performancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been described as a significant moderator on relationships between core jobs features and psychological states results (Saud, 2020). Psychologists who highlight individual development contend that everyone has at least a spark in him of personal growth and development (Senen, Masharyono, & Edisa, 2020). Hackman and Oldham (1975) also maintain out that people with a low personal development need do not understand and acknowledge the possibilities available in the work (Sarkawi et al, 2017).…”
Section: Growth Need Intent As a Moderator Between Job Characteristic...mentioning
confidence: 99%
“…An employee who has high and good performance (work results or work produced) can support the achievement of the goals and objectives set by a company. The performance of an organization depends on the performance of its employees (Senen et al, 2020). However, superiors can play a role in planning, implementing, and controlling an organization.…”
Section: Introductionmentioning
confidence: 99%